Grand Narratives without Master Narratives (Revista Argentina de Musicología, 2018)
Musicology began its life linked to the master narrative of “Western music”, understood as a subject with a real, undisputed existence and a history that it endeavored to narrate in the manner that a novel tells the story of a hero. The gradual refinement that the discipline underwent along the first half of the twentieth century did not carry with it a questioning of that concept. After midcentury, two processes of almost opposite spirit combined to undermine it: scientism and postmodern trends. Both contributed to rob the prior narrative model of its prestige and to disparage any attempt at comprehensive narratives embracing long periods and wide areas. In this paper I attempt to sort out and differentiate the master narratives criticized by Lyotard from the need to build the wide-ranging narrations that the discipline needs. On the basis of the theories of Rick Altman, I propose a model of multi-focal narrative that avoids some of the pitfalls of the mono- or bifocal accounts we have been relying on.
Keywords: Master Narratives; Narrativity; Musicology; Grand Narratives